INTERNALISASI NILAI KERAHMATAN DALAM SURAT AL ANBIYA AYAT 107 PADA PENDIDIKAN BERBASIS KOMUNITAS - Irfa Afrini; Yuli Safarin; Raihana Fadhila (STAI Dirosat Islamiyah Al-Hikmah Jakarta, 2024)
This journal goes into the process of internalizing the values of grace found in Al-Anbiya Verse 107, which tells of how God loves all that He creates. The aim of this study is to examine the meaning and influence of such values of kindness in education, especially in the context of community-based education. This study shows through the analysis of the Qur'an texts that values of mercy such as compassion, mercy, and justice have a significant relationship with the development of a person's character in community-based education. The results of this research drive positive educational change. It is hoped that those who are engaged in community-based education can become agents of change that are more conscious of God's grace and can help shape more peaceful and resilient societies. Verse 107 of Al-Anbiya can be insight and inspiration.